Modulation of auditory deviance detection by acute nicotine is baseline and deviant dependent in healthy nonsmokers: a mismatch negativity study. (9th July 2014) - Knott, Verner; Impey, Danielle; Philippe, Tristan; Smith, Dylan; Choueiry, Joelle; de la Salle, Sara; Dort, Heather
<x xml:space="preserve">Abstract</x> Objective Cognitive enhancement resulting from nicotinic acetylcholine receptor stimulation may be evidenced by increased efficiency of the auditory‐frontal cortex network of auditory discrimination, which is impaired in schizophrenia, a cognitive disorder associated with excessive tobacco use. Investigating automatic (preattentive) detection of acoustic change with the mismatch negativity (MMN) brain event‐related potential in response to nicotine in individuals with varying baseline levels of auditory discrimination may provide useful insight into the cholinergic regulation of this neural network and its potential amelioration with novel nicotinic agents. Methods Sixty healthy, non‐smoking male volunteers were presented with an 'optimal' multi‐feature MMN paradigm in a randomized, placebo controlled double‐blind design with 6 mg of nicotine gum. Results Participants with low, medium, and high baseline amplitudes responded differently to nicotine (vs. placebo), and nicotine response was feature specific. Whereas MMN in individuals with high amplitudes was diminished by nicotine, MMN increased in those with low amplitudes. Nicotine effects were not shown in medium amplitude participants. Conclusions These findings provide preliminary support for the role of nicotinic neurotransmission in sensory memory processing of auditory change and suggest that nicotinic receptor modulation can both enhance and diminish change detection, depending on baseline MMN and its eliciting stimulus feature. Copyright © 2014 John Wiley & Sons, Ltd.